Effects of intrinsic motivation on hotel employees job satisfaction - Mahdzar, Mazlina; Abd Gani, Arni; Isa, Siti Suriawati (Human Resource Management Academic Research Society, 2023)
This study aims to examine the motivational effects that affect job satisfaction among operational hoteliers. The rapid growth of the hospitality industry, mainly the hotel sector, has made employee commitment one of the rising issues in the hotel industry. This research examines the relative effects of intrinsic motivation factors on job satisfaction among hotel employees to understand the lead factor of employee commitment. The sample of the study was 384 hotel employees working in four stars and five stars rating hotels in Malaysia. The methods of data analysis used are descriptive and multiple regression. The results show that Job Security, Achievement, Job Responsibility, and Work Itself significantly affect job satisfaction. The findings of the research are discussed from the viewpoint of hotel employees.